Assessing the Biofumigation Efficacy of Cabbage Residue Against Root Knot Nematodes in Tomato Cultivation - David Japhet; Goru Donovan; Liet Zechariah; Mohamed Aezeden (SHS Web of Conferences)
Root knot nematode (Meloidogyne spp.) are known to damage the roots of many plants, including tomato, and reduce their ability to obtain water and nutrients from the soil resulting in reduced yield. Currently, numerous environmentally friendly root nematodes management approaches have been developed, with biofumigants being one of them. This research project aims to evaluate the bio fumigation effects of cabbage refuse on root knot nematodes affecting tomato (Solanum lycopersicum) plants. Biofumigation is a strategy that uses plants from the brassica family, such as cabbage waste to produce chemicals called glucosinolates, which are broken down into isothiocyanates that can suppress antagonist pathogens affecting crops. The experiment was set up in a completely randomized design, with four treatment combinations of soil and cabbage. The results show that the addition of cabbage refuse with sterilized soil had a significant influence on the growth and canopy cover of tomato plants compared to other treatments. Biofumigation has become a popular non-chemical alternative to control nematode pests in recent years, and studies have shown that it can effectively suppress plants parasitic nematode without compromising soil health. Organic amendments, resistant varieties, crop rotation, and cultural practices are other management practices that that can reduce the risk of root knot nematodes. Plant parasitic nematodes are regarded as one of the main issues restricting the yield of crops on a global scale, affecting food security due to the anticipated increase in population and dietary changes.